Dynamic modulated Gaussian pulse propagation within the double PANDA ring resonator system - Uomwech, K.; Sarapat, K.; Yupapin, P. P. (My University, 2010)
We propose the interesting results of light pulse propagation within a double PANDA ring resonator system. We use the technique of finite difference time domain that is implemented by the scientific programming method known as OPTI-WAVE PROGRAMMING to simulate and analyze the dynamic wave forms of propagating light pulse within the desired system. By using the input Gaussian pulse with center wavelength at 1550 nm and the other practical parameters into the system, results obtained have shown that the multiwavelength light sources can be generated and achieved, and the dynamic behaviors of light pulses propagating within the system can be seen. © 2010 Wiley Periodicals, Inc.
Keywords: Dynamic wave forms; Integrated optic device; Optical components; Ring resonator